Student Voice Assessing Oral Presentations In Virtual and Physical Settings - Noor Raha, Mohd Radzuan (UMPSA, 2023)
The COVID-19 pandemic has changed traditional educational practices, forcing educational institutions worldwide to transition to online learning platforms rapidly. Instructors and students have no other option but to adapt to new pedagogical approaches that suit the instructional sessions and assessments conducted in virtual settings.